Intertemporal Substitution in the Time Allocation of Married Women - YAMADA, Ken (Institutional Knowledge at Singapore Management University, 2011)
This paper studies a life-cycle model of home production to examine how married women change their allocation of time in response to evolutionary movements along the life-cycle wage profile in Japan. After accounting for the potential bias due to heterogeneity, measurement error, weak instruments, and missing data, the estimates of intertemporal substitution elasticity obtained from the home production model are moderate and similar to those obtained from the standard labor supply model.